2022
DOI: 10.58661/ijsse.v2i2.42
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Firm Size, Investment Opportunity Set, and Capital Structure on Firm Value

Abstract: The purpose of this study was to examine how business size, investment opportunity set, and capital structure all affect the value of the company. Explanatory research was conducted for this study, which used secondary data in the form of financial statement data from companies in the banking sector listed on the Pakistani Stock Exchange for the ten years 2010–2019. Twenty-seven businesses were selected for the samples throughout the previous ten years using the purposive sampling technique. The AMOS applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…According to Kallapur and Trombley (1999), the calculation must utilize a proxy to identify the IOS because it is not a latent phenomenon that cannot be observed directly. Afridi et al (2022), Ilmiyono et al, (2021), and Frederica (2019) all conducted prior studies on the IOS and discovered empirical evidence that the investment opportunity set positively affects firm value. According to Smith and Watts (1992) and Skinner (1993), businesses with high levels of corporate value, as measured by IOS, have a propensity to employ less debt in their capital structures.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kallapur and Trombley (1999), the calculation must utilize a proxy to identify the IOS because it is not a latent phenomenon that cannot be observed directly. Afridi et al (2022), Ilmiyono et al, (2021), and Frederica (2019) all conducted prior studies on the IOS and discovered empirical evidence that the investment opportunity set positively affects firm value. According to Smith and Watts (1992) and Skinner (1993), businesses with high levels of corporate value, as measured by IOS, have a propensity to employ less debt in their capital structures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Investment Management and Financial Innovations, Volume 20, Issue 2, 2023 http://dx.doi.org/10.21511/imfi.20 (2).2023.07 play an important role in making strategic policies related to the future development of the company, where these policies are used as a basis for determining company policies and operational activities in order to achieve company goals (Frederica, 2019;Afridi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, based on the narrative above, it can be said that PBV, then the company will have such prospects, or it can be said that PBV will increase the value of the firm. Below is a graph of the average PBV movement in the last six years starting from six years ago from 2015 to 2020 now on the LQ45 Index company to find out the business phenomena that occur: Previous research as empirical evidence has concluded that fluctuations in the company's value can occur not only due to external factors but also internal factors of the company [9]. Company owners or high-level management as internal parties of the company are more aware of the conditions of a company.…”
Section: Introductionmentioning
confidence: 99%
“…Company owners or high-level management as internal parties of the company are more aware of the conditions of a company. Therefore their role is to make company policies that can increase the company's value [9] [10]. Investment decisions are proven to be very closely related to company value and are no less important factors in the financial management function [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation